Pelatihan Pendidik Sebaya tentang Generasi Berencana (GenRe) di SMP N 24 Kota Semarang - Sofiyanti, Ida; Astuti, Fitria Primi; Setyowati, Heni (Universitas Respati Yogyakarta, 2020)
The true teenager is the hope of a nation, the country will become strong if it has teenagers who are spiritually intelligent, intellectually and have a strong emotional. As the rapid development of the world makes changes in behavior in adolescents, but these changes are more likely to lead to negative activities rather than positive activities. Problems that often arise are usually related to sexuality issues, such as unwanted pregnancy, abortion, HIV / AIDS, and drug abuse. Adolescents with these behavioral deviations need a treatment and also get information about reproductive health for young women and men, need to organize a good future by leaving unwholesome behavior that can damage the future of adolescents. Going through adolescence far from deviant behavior would certainly be our common concern. Teenagers will not be able to walk on their own without the assistance of parents, the school, home and etc. Realizing this, the Community Service Study Program of the Midwifery Study Program at the Faculty of Health, Ngudi Waluyo University, felt responsible for facilitating adolescents to learn to understand and be able to practice healthy behaviors to become adolescents who had strong hopes for the nation. Community Service is carried out in 5 stages, namely the first phase of selecting active groups of students who are willing to be agents of change for GenRe / willing to be peer educators, theÂ second stage of counseling and training of peer educators. The third stage of mentoring is increasing peer group skills in providing information to peers. Stage four peer educators independently socialize GenRe to peers. The Fifth stage evaluates the delivery of information from peer educators to their peers, explores the usefulness of the existence of peer educators, limitations and new things that arise when becoming a peer educator.Keywords: Generation planning, peer educators